2017
DOI: 10.3389/fnana.2017.00114
|View full text |Cite
|
Sign up to set email alerts
|

Development of Circumventricular Organs in the Mirror of Zebrafish Enhancer-Trap Transgenics

Abstract: The circumventricular organs (CVOs) are small structures lining the cavities of brain ventricular system. They are associated with the semitransparent regions of the blood-brain barrier (BBB). Hence it is thought that CVOs mediate biochemical signaling and cell exchange between the brain and systemic blood. Their classification is still controversial and development not fully understood largely due to an absence of tissue-specific molecular markers. In a search for molecular determinants of CVOs we studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 72 publications
(103 reference statements)
0
16
0
1
Order By: Relevance
“…Given the highly selective permeability properties of the BBB, it was long assumed that cytokines are only able to pass the BBB at the circumventricular organs (CVOs), which are brain structures that lack the impermeable characteristics of the BBB. The latter include the pineal gland, parapineal organ, vascular organ of the lamina terminalis, subfornical organ, paraventricular organ, neuropituitary, median eminence, subcommissural organ, and the area postrema and the choroid plexus [ 137 ]. In support of this theory, lesion studies in rodents indicated that a disruption of specific parts of the CVOs dampens fever, induced by peripheral LPS application [ 389 ], as well as prevents peripheral IL-1β-induced HPA axis activation [ 222 ].…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…Given the highly selective permeability properties of the BBB, it was long assumed that cytokines are only able to pass the BBB at the circumventricular organs (CVOs), which are brain structures that lack the impermeable characteristics of the BBB. The latter include the pineal gland, parapineal organ, vascular organ of the lamina terminalis, subfornical organ, paraventricular organ, neuropituitary, median eminence, subcommissural organ, and the area postrema and the choroid plexus [ 137 ]. In support of this theory, lesion studies in rodents indicated that a disruption of specific parts of the CVOs dampens fever, induced by peripheral LPS application [ 389 ], as well as prevents peripheral IL-1β-induced HPA axis activation [ 222 ].…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…Tol2 transposons have been extensively applied for ET in zebrafish [22,23]. Zebrafish ET transgenics performed with the Tol2 transposon technique could be instrumental for studies of the development of the circumventricular organs in zebrafish and for understanding the molecular mechanisms of diseases such as hydrocephalus in humans [24]. Twelve zebrafish lines with a single copy and tissue- or cell-specific GFP expression were obtained using a Tol2 transposable system containing a minimal mouse metallothionein gene promoter and GFP , and one potential En element was identified [11].…”
Section: Introductionmentioning
confidence: 99%
“…At 36 hpf, camel expression associated with the BVS is obvious. Based on cell morphology and neuroanatomical landmarks and recent analysis (García-Lecea et al 2017 ), the domain corresponding to the most anterior midbrain RP (posterior to epiphysis) corresponds to the SCO (Fig. 3 h, h’).…”
Section: Resultsmentioning
confidence: 83%
“…The ET27 transgenics (Parinov et al 2004;Kondrychyn et al 2009;García-Lecea et al 2017) express GFP in the SCO (Fig. 9a).…”
Section: Camel Regulates Formation Of Bvs In Vivomentioning
confidence: 99%